HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN REMAJA PUTRI DALAM MENGHADAPI MENARCHE - Desti Ramatika Abadi; Ari Pristiana Dewi; Sofiana ' Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Puberty in girlsadolescent is characterized by hormonal changes that the arrival of menarche can caused anxiety. The aim of this research was to determine the relationship of family support with the level of anxiety in adolescent to confronting menarche in elementary school/equivalent at Kelurahan Tuah Karya was descriptive correlation design and cross sectional approachment. The sample are 275 respondent was cluster random samping. The instrument used questionnaire the validity and reliability had been tested. The analyses used are univariat to determine the frequency distribution and bivariate using chi-Square test. The result showed 149 respondents received positif family support was 56 from them experienced mild anxiety (37,6%), 63 respondents had moderate anxiety (42,3%), and 30 respondents experienced severe anxiety (20,1%). A total of 126 respondents received negative family support was 67 of them experienced mild anxiety (53,2%), 48 respondents had moderate anxiety (38,1%), and 11 respondents experienced severe anxiety (8,7%). The statistic result obtained is (0,007) < (α = 0,05), therefore there is significantly relationship of the family support with level anxiety in adolescent girl in confront menarche during elementary school/aquevalent at Kelurahan Tuah Karya Kecamatan Tampan. This research recommend to the nurse for give promotion of healt about menarche that can caused anxiety to adolescent confornt puberty. Keyword                : Adolescent girl, anxiety level, family support